Readiness Evaluation of the eSKoPpi Application for Electronic Correspondence Management System Development at DISKOMINFO Malang City - Linda Suvi Rahmawati; Andri Prasetyo; Aurelia Dewi Mashinta (Universitas Islam Raden Rahmat, Malang, 2026)
Digital transformation in public sector organizations requires effective information systems to improve administrative efficiency and service quality. The Communication and Informatics Office (DISKOMINFO) of Malang City has developed eSKoPpi (Electronic System for Innovative Public Service Competition), a web-based application that provides structured workflows, role-based access control, and comprehensive system documentation. However, it does not support essential electronic correspondence management functions, including letter registration, electronic disposition, digital archiving, and document tracking. This study evaluates the readiness of eSKoPpi for further development into an Electronic Correspondence Management System. A qualitative case study approach was employed using document analysis, direct observation, and semi-structured interviews. The evaluation focused on documentation completeness, workflow suitability, role-based access control, document management capability, and organizational readiness. The results indicate that eSKoPpi provides a strong technical foundation through comprehensive documentation and an established role-based access control mechanism. Nevertheless, several correspondence-specific functionalities remain unavailable. To address these gaps, BPMN-based business process models, UML use case models, and user interface prototypes were developed. The findings demonstrate that eSKoPpi is technically ready for future enhancement and can support digital transformation initiatives in local government administration.